1997
DOI: 10.1210/endo.138.12.5592
|View full text |Cite
|
Sign up to set email alerts
|

A Second Form of Gonadotropin-Releasing Hormone (GnRH) with Characteristics of Chicken GnRH-II Is Present in the Primate Brain1

Abstract: The primate brain was thought to contain only the GnRH known as mammalian GnRH (mGnRH). This study investigates whether a second form of GnRH exists within the primate brain. We found that brain extracts from adult stumptail and rhesus monkeys contained two forms of GnRH that were similar to mGnRH and chicken GnRH-II (cGnRH-II) based on the elution position of the peptides from HPLC and on cross-reactivity with antisera that are specific to mammalian or chicken GnRH-II in RIAs. The fetal brain of rhesus monkey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(30 citation statements)
references
References 45 publications
3
25
0
2
Order By: Relevance
“…The morphology of the GnRH-II-immunopositive cells identi¢ed in this study is consistent with that of GnRH-II neurons previously identi¢ed in other species. In rhesus macaque monkey, GnRH-I-immunopositive cells are characteristically fusiform in shape with thick neurites and the cells containing GnRH-II are smaller and more ovalshaped, with ¢ne, short processes [8]. Our results are consistent with these descriptions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The morphology of the GnRH-II-immunopositive cells identi¢ed in this study is consistent with that of GnRH-II neurons previously identi¢ed in other species. In rhesus macaque monkey, GnRH-I-immunopositive cells are characteristically fusiform in shape with thick neurites and the cells containing GnRH-II are smaller and more ovalshaped, with ¢ne, short processes [8]. Our results are consistent with these descriptions.…”
Section: Discussionsupporting
confidence: 90%
“…Using both immunocytochemistry and in situ hybridization in the tree shrew, Kasten et al [1] also found no overlap in the distribution of neurons containing the two forms of GnRH. In the rhesus macaque, immunocytochemical staining revealed a posterior system of neurons containing GnRH-II that projects throughout the brain to structures including the hindbrain, posterior pituitary, and spinal cord, and an anterior system of neurons containing GnRH-I which project from the hypothalamus to the pituitary or median eminence [8]. Urbanski et al [5] used cRNA probes in the rhesus macaque to identify GnRH-II-expressing neurons in the midbrain, hippocampus, and several regions of the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue sections (15 m) were subjected to the peroxidase͞ diaminobenzidine visualization technique as described (19,20). Fluorescent labeling was accomplished by using the same procedure up to the step before avidin-biotin-complex reaction, when the fluorescein label (Rhodamine 600, avidin D, or FITC) was applied to the slides and incubated at room temperature in the dark for 2-4 h. For double labeling, slides were incubated sequentially with avidin D and biotin blocking solutions for 15 min each, then reincubated with the next primary antibody, followed by the other fluorescent labeling (Rhodamine or FITC).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, GnRH II has been localized to the hypothalamic area in species of non-mammalian vertebrates (see refs. 7 and 8 for review) and the supraoptic, paraventricular, arcuate, and pituitary stalk regions of monkeys, where it is thought to play a role in gonadotropin secretion (20,36). We therefore conducted studies by using a well-established sheep model to determine the relative effects of mammalian GnRH I and GnRH II on LH and FSH secretion.…”
Section: Marmoset Type II Gnrh Receptor Function In the Pituitarymentioning
confidence: 99%